Coupling model and optimal combination scheme of water, fertilizer, dissolved oxygen and temperature in greenhouse tomato under drip irrigation - Ouyang, Zan; Tian, Juncang; Zhao, Ce; Yan, Xinfang (International Journal of Agricultural and Biological Engineering, 2021)
Water-fertilizer coupling technology has been widely used in the world. Poor soil aeration, low temperature or high temperature can affect the rate of nutrient uptake by crop roots. Aiming at the interaction between water, fertilizer, dissolved oxygen and temperature (WFOT) coupling model and irrigation flux of tomato in greenhouse, using these four factors with a five-level uniform-precision rotatable central composite design, a mathematical model was established among the four factors affecting tomato yield in a greenhouse, and the optimal combination scheme of WFOT was obtained. Within the test range, tomato yields increased with increasing irrigation quotas (X1), fertilization amount (X2), dissolved oxygen (X3) and geothermal pipe water temperature (X4). The magnitude of the effect of each factor of WFOT on tomato yield was in the following order: X1, X2, X4, X3 (spring and summer), and X1, X3, X2, X4 (autumn and winter). The interaction between high water-low heat and low water-high heat was beneficial for yield increase (spring and summer), the high fertilizer-low heat and low fertilizer-high heat interactions were beneficial to yield increase (autumn and winter). If WFOT agronomic measures were adopted according to the 95% confidence interval, there was a 95% probability that the spring-summer tomato yield will be higher than 89 902 kg/hm2. The WFOT coupling scheme was X1 of 4808-5091 m3/hm2, X2 (N-P2O5-K2O) of 171-57-84 to 186-62-89 kg/hm2, X3 of 7.9-8.2 mg/L, and X4 of 34.9°C-37.0°C. There was a 95% probability of tomato yield higher than 85 209 kg/hm2 in autumn and winter, and the WFOT coupling scheme was X1 of 5270-5416 m3/hm2, X2 (N-P2O5-K2O) of 151-50-76 to 167-56-82 kg/hm2, X3 of 8.0-8.2 mg/L, and X4 of 34.1°C-36.2°C. Overall, and the model had a very good simulation effect, with application value. The relative error between spring-summer and autumn-winter yields ranged from 1.12% to 25.34%. The results of the study can provide a theoretical basis for improving the quality and efficiency of greenhouse tomatoes. Keywords: aeration irrigation, soil warming, water-fertilizer-dissolved oxygen-temperature coupling model, optimal combination scheme DOI: 10.25165/j.ijabe.20211406.5403 Citation: Ouyang Z, Tian J C, Zhao C, Yan X F. Coupling model and optimal combination scheme of water, fertilizer, dissolved oxygen and temperature in greenhouse tomato under drip irrigation. Int J Agric & Biol Eng, 2021; 14(6): 37–46.